MANIFESTASI PENDIDIKAN KARAKTER PERSPEKTIF KEMDIKBUDRISTEK DALAM NOVEL KAMI (BUKAN) SARJANA KERTAS KARYA J.S. KHAIREN - M. Kholiq Arif Santoso; Abdul Mukhlis (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Abstract The background of this research stems from the efforts made by the government to build the character of the younger generation by instilling 18 character values ​​in students through character-based education. The realization of character education can be done through a learning process using creative media such as novels. One of the novels that contain the value of character education is the novel Kami (Not) Sarjana Kertas by J.S. Khairen. The purpose of writing this research is to identify and describe the value of character education contained in the novel. Based on the methodology, this study is included as library research with a qualitative descriptive approach. The data collection uses the literature study method with the technique of reading, understanding, and analyzing data sources. The data analysis used in this study utilizes content analysis theory. The results of this study indicate that in the novel there are character education values ​​that represent Religious, Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit or Nationalism, Love for the Homeland, Appreciating of Achievement, Communicative, Love Peace, Love to Read, Care for the Environment, Care for Social, and Responsibility. Keywords: Manivestation, education, character, kemdikbudristek, novel